CCL5 Suppresses Klotho Expression via p-STAT3/DNA Methyltransferase1-Mediated Promoter Hypermethylation - Liu, QiFeng; Li, ShaSha; Yu, LiXia; Yin, XiaoYa; Liu, Xi; Ye, JianMing; Lu, GuoYuan (Frontiers in Physiology, 2022)
Background: Enhanced inflammation and reduced Klotho are common features in chronic kidney disease (CKD). Inflammation induces DNA hypermethylation. This study assessed the performance of inflammatory marker C-C motif chemokine 5 (CCL5) in epigenetic regulation of Klotho expression. Methods: The serum CCL5 level, sKlotho level and DNA methylation were evaluated in CKD patients. A renal interstitial fibrosis model with CKD was induced in mice via unilateral ureteral obstruction (UUO) and human proximal tubular epithelial (HK-2) cells treated with CCL5. Methylation-specific PCR was performed to assess DNA methylation of the Klotho promoter. CCL5, Klotho, and DNA methyltransferases (DNMTs) were detected by immunofluorescence or western blotting. HK-2 cells were exposed to CCL5 with or without 5-aza-2ʹ-deoxycytidine (5-Aza), a DNA methyltransferase inhibitor and static, a p-signal transducer and activator of transcription 3 (STAT3) inhibitor, and expressions of p-STAT3, DNMT1 and Klotho were determined by western blotting. Results: CCL5 upregulation concomitant with Klotho downregulation and global DNA methylation were observed in CKD samples. UUO increased the CCL5 level, enhanced Klotho promoter methylation, suppressed Klotho level, activated p-STAT3 signaling and upregulated DNMT1 level. A similar observation was made in HK-2 cells treated with CCL5. More importantly, 5-Aza inhibited UUO-induced Klotho hypermethylation, reversed Klotho and downregulated p-STAT3 expressions in vivo. The consistent findings in vitro were also obtained in CCL5-treated HK-2 cells exposed to 5-Aza and stattic. Conclusion: The CCL5/p-STAT3/DNMT1 axis is implicated in epigenetic regulation of Klotho expression in CKD. This study provides novel therapeutic possibilities for reversal of Klotho suppression by CKD.